History of Gbԑԑnlԑԑ [Gbeenlee] Katoo, Gbao - Anane, James; Stahl, Ann B. (University of Victoria Libraries, 1982)
Oral history of Gbԑԑnlԑԑ [Gbeenlee] Katoo (house), Gbao. This was the first family history recorded as part of the Banda Research Project. The history describes how the Gbԑԑnlԑԑ family came to live in the Banda area, relating also the history of the Brafour segment of the family who live in Ahenkro (Kafͻnͻ/Kafono Katoo). It relays how the Jakari Fetish was brought to the area. Former male and female heads of family are listed. To cite: Stahl, Ann, and James Anane. 2011. Gbɛɛnlɛɛ Katoo, Gbau [Gbao]. In, "Family Histories from the Banda Traditional Area, Brong-Ahafo Region, Ghana, 1986," pp. 11-13. Brochure circulated 1989, reissued with photos and additional histories in 2011. 4 pages.